Toward a New Direct Process: Synthesis of Methylmethoxysilanes from Dimethyl Carbonate and Pentacopper Silicide - Roberts, John M; Pushkarev, Vladimir V; Sturm, Jason J; Katsoulis, Dimitris E (Industrial & engineering chemistry research, 2020)
We disclose the direct synthesis of methylmethoxysilanes from pentacopper silicide, Cu5Si, and dimethyl carbonate, DMC, affording high levels of dimethylsilyl products without the use of halide catalysts. When Cu5Si powder (99.5%) was reacted with DMC at 350 °C, Me2Si(OMe)2 was the major silane product at >70% selectivity. In contrast, when a high purity Cu5Si (99.99%) was used, the reaction afforded mainly permethoxylated silanes. ICP-OES identified several impurity elements in the low purity Cu5Si. By synthesizing materials that contained the individual impurity elements and reacting them with DMC, tin was revealed as being a crucial promoter. XPS revealed that tin segregates to the surface under reaction conditions, and elevated tin levels have a significant impact on DMC reactivity with the surface. XPS also suggests that tin is in the zero oxidation state at the surface, which provides some insight to its role in the direct synthesis of methylmethoxysilanes.